Promoting Multicultural Awareness Through Language Education - Wahyuni, Erna; Normuslim, Normuslim; Siminto, Siminto; Sianipar, Godlif; Hastuti, Erni (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia., 2024)
In today’s increasingly interconnected world, promoting multicultural awareness has become essential, especially in educational settings. Language education offers a unique platform to foster this awareness, as language and culture are deeply intertwined. However, many language programs focus primarily on linguistic skills, overlooking the cultural dimensions that help students appreciate and navigate cultural diversity. This research aims to examine the role of language education in enhancing students’ understanding of multiculturalism, specifically through curricula that incorporate cultural perspectives and foster intercultural competence. A mixed-methods approach was used, combining surveys and interviews with 200 language learners and 50 educators across various educational institutions. Quantitative data from the surveys measured participants' perceptions of multicultural awareness, while qualitative data from the interviews provided deeper insights into how language education influences students' cultural understanding. Both methods were essential to capturing the complex relationship between language learning and multicultural awareness. The findings indicate that students exposed to culturally enriched language curricula showed a higher level of interest in cultural topics and a greater openness toward diverse perspectives. Educators observed that students became more engaged when cultural content was integrated into lessons, improving their overall language proficiency and intercultural skills.